Dampak Konformitas Teman Sebaya Terhadap Motivasi Belajar Dan Prestasi Akademik Siswa - Bismil Selvia; Farhan Julianto; Festy Azkia Fais; Mega Mustika (Simpati, 2024)
Conformity, or the tendency to conform attitudes and behaviors to group norms, can affect students' learning motivation and academic achievement. This article discusses the impact of conformity on students' learning motivation and academic achievement from two sides, namely positive impact and negative impact. On the positive side, conformity within certain limits can help students adapt to the school environment and encourage them to learn to be accepted in the group. But on the other hand, excessive pressure to conform to peers can reduce students' internal motivation to learn and achieve. Students tend to only study as needed to be accepted in the group and their academic performance decreases. Therefore, a balance is needed, where students maintain their uniqueness while adapting positively to the group. Thus, conformity can benefit students' learning motivation and achievement.